Synthesis of wafer-scale SWCNT forests with remarkably invariant structural properties in a bulk-diffusion-controlled kinetic regime. (5th January 2023) - Park, Sei Jin; Moyer-Vanderburgh, Kathleen; Buchsbaum, Steven F.; Meshot, Eric R.; Jue, Melinda L.; Wu, Kuang Jen; Fornasiero, Francesco
Abstract: Robust synthesis of vertically aligned carbon nanotubes (VACNT) at large scale is required to accelerate deployment of numerous cutting-edge devices to emerging commercial applications. To address this need, this work demonstrates that the structural characteristics of single-walled CNTs (SWCNTs) produced in a growth regime dominated by bulk diffusion of the gaseous carbon precursor are remarkably invariant over a broad range of process conditions (precursor concentration increased up to 30-fold, catalyst substrate area from 1 cm 2 to 180 cm 2, growth pressure from 20 to 790 mbar, and gas flowrates up to 8-fold). A simple growth kinetics model is derived that accounts for both reactant bulk diffusion and competing byproduct formation in the presence of excess hydrogen, which quantitatively reproduces the experimental data in the entire isothermal parameter space. The model enables critical predictions for process scale-up optimization including a potential 6-fold increase in CNT production rate, a ∼90% carbon conversion efficiency in select conditions, and elimination of reaction rate decay observed at high pressures by using a hydrogen-free growth environment. This model-guided opportunity to substantially improve synthesis throughput and efficiency, in conjunction with the remarkably invariant CNT properties, is appealing for reliable VACNT device fabrication at both small and industrial scales. Graphical abstract: Image 1 Highlights: Vertically-aligned single-walled carbon nanotube are synthesized at wafer scale. The growth kinetics is dominated by bulk gas diffusion and byproduct formation. Proposed kinetic model quantitatively describes growth kinetics at all conditions. Carbon nanotubes show invariant characteristics in a broad synthetic space.